Tinjauan Kuat Tekan Dan Absorbsi Mortar Yang Mengandung Air Garam: Review Of The Compressive Strength And Absorbtion Of Mortars Containing Baline - Rofikatul Karimah; Khairul Abadi; Mochammad Ridwan; Iklil Lutfiyah Kamila (Media Ilmiah Teknik Sipil, 2023)
Mortar is a building material that serves to glue bricks, bricks, plaster, and so on. As an adhesive, mortar has a viscosity that is useful in determining compressive strength. In the manufacture of mortar, SNI 03-6882-2002 requires the use of clean fresh water, but in reality, as an archipelagic country, some of the islands in Indonesia are isolated from fresh water. As a result, freshwater becomes an expensive item, because it is imported from other areas, so it requires transportation costs. If the mortar is required to use water according to SNI standards, the project implementation costs will be expensive. In areas that do not have adequate fresh water, mortar is made using water obtained on-site, including brackish, salt, and sea water. Seawater contains elements of NaCl salts which can bind Calcium Hydroxide (CaOH) compounds, reducing the CaOH compounds in the mortar will increase the compressive strength of the mortar. In this study, a review of brine as a mixture of mortar materials was carried out with the aim of knowing the performance of mortar containing salt water by compressive strength test and Absorption test. The amount of salt water added to the mortar mixture is 0%; 0.5%; 1%; 1.5%; 2%; 2.5% ; 3%; 3.5% of the volume of water used as a mortar mix. Cube test object measuring 50x50x50 mm3 in the amount of 5 in each treatment, made from a mixture of 1PC: 2.75 Sand (based on weight ratio), with a water-cement factor (FAS) of 0.45. The test results obtained the compressive strength value of the mortar with the addition of salt water can reduce the compressive strength value but the use of brine with a content of 3.5% is still in the category of minimum permissible pressure according to SNI03-6882-2002. While the absorption value of the mortar can increase fiber strength with increasing addition of 3.0% brine.